Responsibilities of Complementary Allies in The Commanditaire Vennootschap (CV) Business Enity ENTITY (Journal of Private and Commercial Law, 2020)
The focus of this research is the Responsibility of Complementary Allies in the Commanditaire Vennootschap (CV) Business Entity. This study aims to determine the responsibilities of complementary allies if the Commanditaire Vennootschap (CV) goes bankrupt, and to find out the responsibilities of complementary allies in the agreement made if the Commanditaire Vennootschap (CV) fails. This study uses a normative juridical research method using a statutory approach and a conceptual approach using primary and secondary legal materials related to the research focus, then it is analyzed qualitatively descriptively. The result of this research is that if the CV is declared bankrupt, all of CV's assets are collateral for the settlement of CV's debt. Personal assets of complementary partners can be accounted for to pay off all debts of the CV. If the CV is in default, the one who must be responsible is complementary allies. This responsibility is in the form of compensation to creditors as a consequence of default by CV to private assets of limited partnership because the CV is not a legal entity that has separate characteristics of its assets from its management.